Transformation of Islamic Boarding School Education: Integration of Trilogy Values and Five Student Awareness in Curriculum Development - Zubaidi, Ahmad; Naura Fikroh Sadidah; Muhammad Khairul Umam (Edukasia Islamika : Jurnal Pendidikan Islam, 2024)
This research investigates the transformation of pesantren education through the reinforcement of core values, which are realized and implemented in various programs at pesantren. Employing a qualitative case study methodology, the study systematically explores pertinent issues, analyzes data, and presents findings. The focal point of this research is Nurul Jadid University (UNUJA), an Islamic boarding school located in Probolinggo, which has consistently upheld the Trilogy and Five Awareness of Students since its establishment. These values are not merely rhetorical but function as foundational guidelines for curriculum development, ensuring their application across all institutional levels. The research is structured into two primary segments: (1) the Trilogy paradigm and Five Awareness of Students, and (2) the implementation of the transformation of pesantren education through curriculum development at UNUJA. The results show that UNUJA preserves these values through five strategic initiatives: (1) integrating the pesantren curriculum with university courses by incorporating local content, (2) providing extracurricular programs to enhance student competencies, (3) organizing seminars, workshops, and public discussions, (4) executing the Merdeka Belajar-Kampus Merdeka (MBKM) program while upholding pesantren values, and (5) enforcing campus regulations through an ethics court for both lecturers and students. The study suggests that UNUJA effectively integrates pesantren values with contemporary educational practices, thereby reinforcing its identity as a pesantren-based university. This approach yields graduates who are both ethically grounded and professionally competent, presenting a sustainable model for Islamic educational institutions as they navigate the challenges of modernization. The framework established by UNUJA serves as a valuable reference for other pesantren seeking to balance tradition with innovation.